Tangled history of the European uses of Sphagnum moss and sphagnol. (14th September 2017) - Drobnik, Jacek; Stebel, Adam
Abstract: Ethnopharmacological relevance: Sphagnum mosses and peat could have been utilized as wound dressings for centuries, however reliable data on this subject are ambiguous; sometimes even no distinction between peat moss ( Sphagnum spp.) and peat is made or these terms become confused. The first scientific account on surgical use of peat comes from 1882: a peat digger who successfully, by himself and in the way unknown to the then medicine, cured an open fracture of his forearm with peat. The peat, and very soon the peat moss itself (which is the major constituent of peat) drew attention of the 19th-century surgeons. Aims of the work: We search for reliable information on: (1) inspirations for Sphagnum usage for medical purposes and its beginnings in the 19th century, (2) substances or products named sphagnol and their connections with (1); (3) on the origin of this name, (4) and on the occurrence of this name in medical sources. Materials and methods: We have identified and studied published sources on the uses of peat-based and Sphagnum -based preparations and products of any processing level (including herbal stock, distillate, isolated pure or impure active principle, or a mixture of such) in surgery, pharmacy or cosmetics. A special attention was paid to the name sphagnol, which appeared many a time, in more than one context since 1899. Source publications were critically analysed from the taxonomical, pharmacognostical and ethnopharmacological points of view. Gathered data were cross-checked with the modern knowledge of the biologically active principles of Sphagnum and the prospects of their medical use. Results: The application of peat in surgery started 1882. The use of peat moss as dressings was developed in the 1880's. It returned to surgical practice during WW1. The name sphagnol has two meanings: (1) A chemical substance isolated from the cell walls of Sphagnum mosses in 1899. A post-1950 research showed it to be a mixture of phenols dominated by sphagnum acid. (2) A product of dry distillation of peat contains solid and liquid fractions and was applied in skin diseases due to antiseptic properties. It was added to ointments and medicated soaps manufactured up to the late 1960's. Today none of these two sphagnols is in use. Conclusions: Surgical application of peat had an ethnopharmacological origin: a case of wound treatment with peat as a remedy rather than a dressing (1880, published 1882) shortly shifted the surgeons' attention to peat moss as an absorptive dressing. The 1880's tests of antiseptic properties of peat and peat moss failed, the sterilization methods overrode the physiological effects of Sphagnum dressings. Sphagnan, a polysaccharide from Sphagnum cell walls, discovered 1983, inhibits microbial growth, tans the collagen and removes ammonia from microbial environments. Portions of raw peat could be sterile. The isolation of sphagnol (1899) from Sphagnum cell walls was not inspired by old surgery. Main component of sphagnol, the sphagnic acid, was used clinically during WW2, but was proved a weak antimicrobial agent. A homonymous name sphagnol appeared independently for a product of dry distillation of peat, introduced commercially probably about 1899, too, which gave rise to confusions: a) the commercial, "distilled" sphagnol was not the crystalline principle of Sphagnum cell walls. 2) the "distilled" sphagnol was hardly defined technologically or pharmacologically, never standardized in terms of the substrate (a variety of peat rather than Sphagnum herb) and the production process. This sphagnol, resembling pitch or tar, was an additive to medicated soaps and ointments for skin treatment and care. It must have been a low-scale product although advertised worldwide. Neither sphagnum acid nor sphagnan are used medicinally today. Graphical abstract: